Essays on the limits of borrowing - Risto Herrala (Bank of Finland, 2012)
Chapter 1 Introduction 11 Chapter 2 Reserve pools 23 Chapter 3 Public intervention and financial crises: an empirical study 43 Chapter 4 Credit conditions and durable consumption: evidence of a strong link 67 Chapter 5 The influence of bank ownership on credit supply: evidence from Russia's recent financial crisis 89 Chapter 6 Conclusions 109
URN:NBN:fi:bof-201408071693
Keywords: G2; G3; E5; 330; Kreditrationierung; Lender of Last Resort; Privater Haushalt; Kreditpolitik; Privater Konsum; Bank; Eigentümerstruktur